2012
DOI: 10.1590/s0103-05822012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre ganho de peso no primeiro ano de vida com excesso de peso e adiposidade abdominal na idade pré-escolar

Abstract: OBJETIVO: Avaliar se a mudança no escore Z do índice de massa corpórea por idade >0,67 no primeiro ano de vida se associou ao excesso de peso na idade pré-escolar. MÉTODOS: Estudo de coorte aninhado a ensaio de campo randomizado realizado na cidade de São Leopoldo, no Rio Grande do Sul. Foram coletados dados de peso e estatura das crianças ao nascimento, dos seis aos oito meses e dos 12 aos 16 meses. Aos três e aos quatro anos, além destes dados aferiu-se a circunferência da cintura. Calculou-se o ganho de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
4
0
2
Order By: Relevance
“…However, it is worth highlighting that, although the higher prevalence is eutrophic children (70.3%), a high prevalence of overweight children (overweight, obesity and severe obesity), around 28% of the sample, can also be observed. Several other studies corroborate this finding 3,9,14,15 , also indicating, in particular, the larger number of school children with appropriate BMI. However, in a study by Nobre et al 16 , while the majority of their sample showed adequate nutritional status for age, their results diverge from the results of the present study in terms of reports that the condition of thinness or severe thinness was larger than the conditions of overweight and obesity.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, it is worth highlighting that, although the higher prevalence is eutrophic children (70.3%), a high prevalence of overweight children (overweight, obesity and severe obesity), around 28% of the sample, can also be observed. Several other studies corroborate this finding 3,9,14,15 , also indicating, in particular, the larger number of school children with appropriate BMI. However, in a study by Nobre et al 16 , while the majority of their sample showed adequate nutritional status for age, their results diverge from the results of the present study in terms of reports that the condition of thinness or severe thinness was larger than the conditions of overweight and obesity.…”
Section: Discussionsupporting
confidence: 59%
“…This accelerated growth takes place mostly as a result of health conditions in children's first two years of life, classifying this time as essential for a child's healthy growth and emphasizing a large number of newborns with weight above the normal. In addition, the duration of breastfeeding, as well as complementary feeding, is considered essential and can interfere directly in growth, reflecting on the BMI in future ages 14 .…”
Section: Discussionmentioning
confidence: 99%
“…O ganho de peso na infância é um fator determinante para o estado nutricional quando adulto (7) . A prevalência de pré-obesidade e obesidade infantil continuam a aumentar de forma significativa no mundo, tornando-se causas de grande apreensão em termos de saúde pública (27) .…”
Section: Discussionunclassified
“…O AM, principalmente o exclusivo, tem efeito protetor contra doenças ocasionadas em crianças que nasceram com baixo peso (<2.500g) (4) , além de estabelecer o vínculo afetivo entre mãe e filho, ajudando no desenvolvimento da criança (5) . O AM ainda atua na proteção contra o sobrepeso e a obesidade durante toda a infância, independentemente da idade da criança, da renda familiar, do estado nutricional e da escolaridade dos pais (6) .No entanto, a alimentação complementar iniciada fora de época pode acarretar no abandono do aleitamento materno, observando que a alimentação nos primeiros anos de vida é fundamental para o crescimento e ganho de peso na infância (7) . O ganho de peso durante os primeiros anos de vida é um fator determinante para o estado nutricional na infância e adolescência.…”
Section: Introductionunclassified
“…Additionally, longitudinal studies conducted in Sweden, Germany, Australia, the USA, Denmark and Brazil have reported that breastfeeding for a longer duration was associated with a decreased risk of maternal postpartum excess body weight (1,18,22,(25)(26)(27)(28) . Other studies, however, have reported small or no protective effects of breast-feeding duration on obesity in children (10,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) or in women after delivery (37) .…”
mentioning
confidence: 97%